Cell membrane camouflaged biomimetic nanoparticles: Focusing on tumor theranostics - Li Zhu; Yuan Zhong; Shuai Wu; Meng Yan; Yu Cao; Nianlian Mou; Guixue Wang; Da Sun; Wei Wu (Materials Today Bio, 2022)
Nanoparticles (NPs) modified by cell membranes represent an emerging biomimetic platform that can mimic the innate biological functions resulting from the various cell membranes in biological systems. researchers focus on constructing the cell membrane camouflaged NPs using a wide variety of cells, such as red blood cell membranes (RBC), macrophages and cancer cells. Cell membrane camouflaged NPs (CMNPs) inherit the composition of cell membranes, including specific receptors, antigens, proteins, for target delivering to the tumor, escaping immune from clearance, and prolonging the blood circulation time, etc. Combining cell membrane-derived biological functions and the NP cores acted cargo carriers to encapsulate the imaging agents, CMNPs are widely developed to apply in tumor imaging techniques, including computed tomography (CT), magnetic resonance imaging (MRI), fluorescence imaging (FL) and photoacoustic imaging (PA). Herein, in this review, we systematically summarize the superior functions of various CMNPs in tumor imaging, especially highlighting the advanced applications in different imaging techniques, which is to provide the theoretical supports for the development of precise guided imaging and tumor treatment.